#### Answer

$\frac{6}{m}$

#### Work Step by Step

If we want to get the common ratio, we just have to divide any two subsequent terms:
$r=\frac{a_2}{a_1}=\frac{\frac{6}{m^2}}{\frac{1}{m}}=\frac{6m}{m^2}=\frac{6}{m}$

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$\frac{6}{m}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.